Comparative analysis of the diagnostic efficiency of the four thyroid imaging reporting and data systems - Jun Xu; Wei-Bing Zhang; Wen-Fang Deng; Bei-Li He; Ting-Yue Qi (WFUMB Ultrasound Open)
The purpose of this study was to comparative analyze the diagnostic efficiency of Thyroid Imaging Reporting and Data System proposed by Kwak, American College of Radiology, the European Thyroid Association and the Chinese Medical Association, respectively (Kwak TI-RADS, ACR TI-RADS, EU-TIRADS and C-TIRADS, respectively) for malignant risk stratification of thyroid nodules. A total of 1142 thyroid nodules confirmed by cytological or surgical pathologies were retrospectively classified according to Kwak TI-RADS, ACR TI-RADS, EU-TIRADS and C-TIRADS. The area under the receiver operating characteristic curve (AUC), the diagnostic sensitivity, specificity, Youden index, and accuracy of each TI-RADS for nodules was calculated and compared. The diagnostic sensitivity of ACR TI-RADS was 85.5%, which was lowest (all P < 0.05). The diagnostic specificity of ACR TI-RADS was higher than that of Kwak TI-RADS and EU-TIRADS (all P < 0.05), but there was no significant difference compared with that of C-TIRADS (x2 = 2.335, P = 0.126). The diagnostic accuracies of the four methods were more than 85%, and there were no significant differences (all P > 0.05). The AUC of C-TIRADS was highest among the four methods (all P < 0.05). The four methods have high diagnostic efficiency in malignant risk stratification of thyroid nodules, and the AUC of C-TIRADS was higher than that of the other three methods.